2021
DOI: 10.1038/s41598-021-98809-9
|View full text |Cite|
|
Sign up to set email alerts
|

The biochemical subtype is a predictor for cognitive function in glutaric aciduria type 1: a national prospective follow-up study

Abstract: The aim of the study was a systematic evaluation of cognitive development in individuals with glutaric aciduria type 1 (GA1), a rare neurometabolic disorder, identified by newborn screening in Germany. This national, prospective, observational, multi-centre study includes 107 individuals with confirmed GA1 identified by newborn screening between 1999 and 2020 in Germany. Clinical status, development, and IQ were assessed using standardized tests. Impact of interventional and non-interventional parameters on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
(82 reference statements)
0
33
0
Order By: Relevance
“…While the first guideline mostly included grade D and a few grade C recommendations, reflecting significant uncertainty (59), the level of evidence and grade of recommendations have been improved continuously, demonstrated by the first (60) and second revision (61). This progress was much accelerated by careful long-term follow-up of national and international cohorts (38,56,57,59,(61)(62)(63)(64)(65)(66)(67)(68)(69), demonstrating that (i) newborn screening is the prerequisite of favorable neurological outcome and survival and (ii) is highly cost-effective, and that (iii) adherence to recommended maintenance and emergency treatment is associated with the most favorable neurological outcome and (iv) normal growth. Furthermore, these studies described a so far unknown renal disease manifestation, unraveled similarities (risk of striatal necrosis with concomitant complex movement disorder with predominant dystonia) and discrepancies (cognitive function, white matter changes, subdural hematoma) between biochemically delineated subgroups (high versus low excreter phenotype), and evaluated which part of the complex clinical spectrum can be specifically targeted and changed by current therapy, highlighting the need for safer and more effective medicines.…”
Section: Guideline Developmentmentioning
confidence: 99%
“…While the first guideline mostly included grade D and a few grade C recommendations, reflecting significant uncertainty (59), the level of evidence and grade of recommendations have been improved continuously, demonstrated by the first (60) and second revision (61). This progress was much accelerated by careful long-term follow-up of national and international cohorts (38,56,57,59,(61)(62)(63)(64)(65)(66)(67)(68)(69), demonstrating that (i) newborn screening is the prerequisite of favorable neurological outcome and survival and (ii) is highly cost-effective, and that (iii) adherence to recommended maintenance and emergency treatment is associated with the most favorable neurological outcome and (iv) normal growth. Furthermore, these studies described a so far unknown renal disease manifestation, unraveled similarities (risk of striatal necrosis with concomitant complex movement disorder with predominant dystonia) and discrepancies (cognitive function, white matter changes, subdural hematoma) between biochemically delineated subgroups (high versus low excreter phenotype), and evaluated which part of the complex clinical spectrum can be specifically targeted and changed by current therapy, highlighting the need for safer and more effective medicines.…”
Section: Guideline Developmentmentioning
confidence: 99%
“…Recommended treatment, if introduced and monitored by an experienced multi‐professional team, is safe and the major prerequisite of good neurological outcome, while deviation from recommended treatment increases the risk of striatal damage, 50,87,90,91 highlighting the importance of the quality of therapy 60 . Some lately recognized aspects of the disease, however, such as chronic kidney disease, 50 progressive white matter changes, 92,93 and slightly reduced IQ in high excreters, 91 do not seem to be impacted by currently available therapies. Besides GA1, this iterative approach of longitudinal observational studies conducted by international scientific consortia and concomitant guideline development is also successfully applied to other IMDs, such as methylmalonic and propionic aciduria, 53,94–96 urea cycle disorders, 57,58,97 cystathionine beta‐synthase deficiency, 98 remethylation disorders, 54,99,100 and tetrahydrobiopterin deficiencies 56,101 …”
Section: Lessons Learned From Long‐term Observation Of Newborn Screen...mentioning
confidence: 99%
“…87,90 Almost 20 years later, there is now solid evidence that GA1 is a treatable NBS condition. Recommended treatment, if introduced and monitored by an experienced multi-professional team, is safe and the major prerequisite of good neurological outcome, while deviation from recommended treatment increases the risk of striatal damage, 50,87,90,91 highlighting…”
Section: To Treat or Not To Treat? And How?mentioning
confidence: 99%
“…This striatal injury often results in MD with predominantly dystonic/dyskinetic features 9 . Initially it was thought that intellect is unaffected in GA1, 10 but recent studies have shown that cognitive impairment is a feature, and that it is predicted by high excretor status 11 . Due to the early presence of subdural effusion, GA1 has been previously misdiagnosed in children as non‐accidental injury 12 …”
Section: Introductionmentioning
confidence: 99%
“…13 Traditionally it was thought that all biochemical phenotypes had a similar clinical course but recent evidence has emerged that HE patients are at increased risk of progressive white matter damage in later life, although the clinical significance of this is unknown. 11,14 Insidious onset GA1 describes striatal injury and MD occurring without apparent crisis and is estimated to account for 20% of symptomatic presentations. 9,15 This phenotype has also been described in patients diagnosed by newborn screening (NBS) with suboptimal adherence to dietary regimes, in whom it may account for up to 50% of cases of MD.…”
mentioning
confidence: 99%